HUBUNGAN ADIKSI PENGGUNAAN SMARTPHONE DENGAN TINGKAT DEPRESI PADA REMAJA RW 014, KELURAHAN SUKAMAJU BARU, KOTA DEPOK - Christin Maria (2021)
Adolescents generally use smartphones to do assignments and communicate with friends or family. Uncontrolled smartphone use can cause any negative impacts, the example is depression. This study aims to determine the relationship between smartphone use addiction and depression levels in adolescents in RW 014 Kelurahan Sukamaju Baru, Kota Depok. This study used a cross sectional research design with total sampling method. The sample of this study was screened first based on the time of smartphone use and the physical problems by respondents, from a total population of 102 respondents, the research sample obtained was 98 teenagers RW 014 Kelurahan Sukamaju Baru, Kota Depok aged 12-20 years who experienced smartphone addiction. The research instrument used the Smartphone Addiction Scale-Short Version (SAS-SV) questionnaire to measure the level of smartphone addiction and the Beck Depression Inventory II (BDI-II) to measure the level of depression. In data analysis using the chi-square test, the Pearson chi-square value was obtained at 0.001 <0.05, which indicates that there is a significant relationship between smartphone addiction and depression levels in adolescents in RW 014 Kelurahan Sukamaju Baru, Kota Depok. Adolescents must be able to control themselves when using smartphones so it won't cause any negative effects for them.